ROLE OF GRAPHENE DEFECTS IN HYDROGEN ADSORPTION (Scientific journal of the Fergana State University, 2024)
Research on hydrogen storage using carbon-based nanomaterials is currently attracting increasing interest. Yet,understanding the storage nature of graphene surfaces is still elusive.In this study, we investigated the physisorption mechanisms of H2 molecules on defective graphenes usingreactive molecular dynamics simulations. We found that an increase in the size and concentration of defects in grapheneincreases the physisorption of H2 molecules on the surface due to a change in the partial charges of atoms in thesystem. Specifically, our results showed that in the case of the highest percentage of defects (10.27%), the gravimetricdensity of H2 molecules is about 2.12 wt.% at ambient conditions, which is within the range of gravimetric densitiesobtained from experiments and other simulations. The results also indicated that the physisorption of H2 molecules isrelated to both the size and the concentration of defects on the graphene surface. This study contributes to a better understanding of the mechanisms of hydrogen storage in graphene withvarious defects at the atomic level.